2016
DOI: 10.1589/jpts.28.2763
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the recovery of activities of daily living after hospitalization for acute medical illness: a prospective cohort study

Abstract: [Purpose] This study investigated the factors associated with the recovery rate of activities of daily living of elderly patients hospitalized for acute medical illness. [Subjects and Methods] A total of 238 elderly patients were enrolled in this study. The main outcome measure was the functional independence measure score which was used as an assessment of activities of daily living. The participants were divided into 2 groups based on their activities of daily living before onset: the independent group and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
(29 reference statements)
1
6
0
Order By: Relevance
“…The results of this study similar to several prior studies reported that ≥ 50% of hospitalized among older patients do not walk outside their room except during rehabilitation or medical examinations [30,31]. Goto et al [32] reported that HAD occurred in several diseases associated with cognitive impairment, frailty, and low physical function. A previous study reported that improvement in ADL is not possible among older patients with frailty, even if early rehabilitation is performed during hospitalization, due to their living environment before hospitalization [33].…”
Section: Discussionsupporting
confidence: 88%
“…The results of this study similar to several prior studies reported that ≥ 50% of hospitalized among older patients do not walk outside their room except during rehabilitation or medical examinations [30,31]. Goto et al [32] reported that HAD occurred in several diseases associated with cognitive impairment, frailty, and low physical function. A previous study reported that improvement in ADL is not possible among older patients with frailty, even if early rehabilitation is performed during hospitalization, due to their living environment before hospitalization [33].…”
Section: Discussionsupporting
confidence: 88%
“…The association between nutritional status (MNA or MNA-SF) and functional parameters (BI or FIM) was analyzed in ten studies (Online Resource 12). Seven [31,33,34,69,76,81,82] out of ten studies reported a significant association between either low MNA or low MNA-SF and low BI or low FIM. One study [30] did not show an association and in two studies [54,64] heterogeneous outcomes were observed.…”
Section: Association Between Nutritional Status and Functional Statusmentioning
confidence: 97%
“…These results are in line with other studies, where the direct association between nutritional status and functional outcomes in hospital-deconditioned patients was unclear. Goto et al [ 54 ] reported that a better MNA-SF score at the start of rehabilitation was only significantly associated with functional recovery in deconditioned patients who were previously more dependent for activities of daily living, while in more independent patients, better nutritional status was not an independent factor for predicting better functional outcomes. In contrast, Katano et al [ 42 ] reported higher functional gain in patients with worse nutritional status (MNA-SF ≤ 7) than in those with better nutritional status (MNA-SF > 7).…”
Section: Discussionmentioning
confidence: 99%